Removal of Emulsified Paraffine from Water: Effect of Bubble Size and Particle Size on Kinetic of Flotation - A. Mohammed, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
This paper studied kinetics of flotation of emulsified paraffine in water in bubble column with sodium .dodecylsulphate as a collector agent. The effects of oil drops and air bubble diameters on the flotation rate constant were studied. The removal rate for each oil drop size was first order with respect to oil drop concentration. An experimental procedure permitting determination of the first order rate constants for removal due to bubble/drop interaction was developed, decreasing bubble diameter by adding NaCl and increasing oil drop diameter increased the rate constants. A comparison between the experimental and theoretical rate constants showed that the predicted mechanism of oil-droplet removed by bubbles less than 1.8 mm diameter is one of hydrodynamics capture in the wake behind the rising bubbles.